Practical JSF in Java EE 8 Web Applications ​in Java for the Enterprise - Müller, Michael (Apress, 2018)
This is an enhanced practical, projects-driven guide to web development with the Java EE 8 and JSF (JavaServer Faces) APIs and web framework. This book combines the theoretical background with a practical approach by building 4 real world applications. By developing these JSF web applications, you'll take a tour through the other different Java EE technologies like JPA, CDI, Security, WebSockets, and more. In this book, you will learn to use the JavaServer Faces web framework in Java EE 8 to easily construct a web-based user interface (UI) from a set of reusable components. Then, you add event handling that JSF also offers and then link to a database, persist data, add security and other "bells and whistles" that Java EE 8 platform has to offer towards building complete enough running web applications. The goal of this book is to create a good foundation in Java-based web development and take you to a more sophisticated level and be proficient i n Java EE 8 web development using the JSF framework. After reading this book, it can serve as an invaluable reference with four takeaway web applications that can be used as templates for your own web projects. What you'll learn: What is in the Java EE 8 and the JavaServer Faces APIs and how to use these to build Java-based web applications through four different and practical real world case studies Process user input with JSF and the expression language by building a calculator application How to persist data using JSF templating and Java Persistence to manage a book store inventory Build and manage a music library with JSF lifecycle, BeanValidation and more Create and manage an alumni database and mailing list using JSF, AJAX, web services and Java EE 8's security features. Who is this book for: This book is for those who are new to Java EE 8, JSF. This book could be for those with some prior experience with Java EE 7 and JSF but want a refresher using latest versions of Java EE and JSF APIs. Some prior experience with Java like Java SE or core JDK is recommended though.